PERAN GOOD CORPORATE GOVERNANCE DALAM MEMINIMALISIR TERJADINYA FINANCIAL DISTRESS - Sa’diah, Wulan Maulidiss; Utomo, Mohamad Nur (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of managerial ownership, independent board of commissioners, board of directors, and audit committee on financial distress in banking companies listed on the Indonesia Stock Exchange from 2015 to 2019. This research used the purposive sampling method with a sample of 41 companies consisting of 205 observational data. Data were analyzed using logistic regression. The results showed that independent board of commissioners and board of directors had a significant and negative effect on financial distress. However, managerial ownership and audit committee did not have a significant effect on financial distress. This study supports the agency theory, which states that the monitoring role of the independent board of commissioners and the board of directors can minimize the occurrence of agency conflicts in a company. Keywords: audit committee, board of directors, financial distress, independent board of commissioners, managerial ownership